Study of GHz-SAM sensitivity to delamination in BEOL layers. (September 2017) - Khaled, A.; Ključar, L.; Brand, S.; Kögel, M.; Aertgeerts, R.; Nicasy, R.; De Wolf, I.
Abstract: Two different back-end-of-line (BEOL) stacks were indented using Berkovich and wedge tips with different indentation forces to simulate failure modes such as cracks and delamination. The indentation areas were investigated by acoustic GHz-microscopy for the detection of these defects. For validation, results were correlated to the SEM images of FIB-prepared cross-sections through the indented areas and their topologies were measured. The acoustic GHz-microscope proves to be a promising tool for the visualization of crack- and delamination defects on a scale of below 10 μm and shows a great potential for BEOL mechanical strength analysis. Highlights: Induced failures in two Back-End-Of-Line stacks using nano-indentation were investigated using acoustic GHz microscopy. The GHz-SAM potential sensitivity toward delamination detection in BEOL stacks is discussed. The acoustic GHz-microscope proves to be a promising tool for the visualization of BEOL defects on a scale of below 10 µm.